2016
DOI: 10.1016/j.ijmyco.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Mixed metal oxide nanoparticles inhibit growth of Mycobacterium tuberculosis into THP-1 cells

Abstract: Although Ag NPs exhibited low cytotoxicity, they were unable to inhibit Mtb growth in vitro. ZnO NPs exhibited strong anti-Mtb activity and inhibited bacterial growth, but exhibited high cytotoxicity to human macrophage cells. By mixing Ag and ZnO NPs at a ratio of 8/2, we acquired a mixture that exhibited potent antibacterial activity against Mtb and no cytotoxic effects on THP-1 cells, resulting in inhibition of both in vitro and ex vivo Mtb growth Figs. 1-3, Tables 1-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The toxicity of the QDs in THP-1 leukemic cells was also studied. Results showed that the 8ZnO/2Ag ratio was the most effective since it had high antibacterial capacity against Mtb both in vivo and in vitro but without affecting the cellular viability of THP-1 cells [ 81 ]. In 2016, R. Jalal et al used different techniques (fluorescence and scanning electron microscopy, flow cytometry and DNA extraction) to elucidate the mechanism of action of ZnO QDs administered alone and in combination with two antibiotics ciprofloxacin and ceftazidime.…”
Section: Zno Nanoplatforms For Bacterial Infectionmentioning
confidence: 99%
“…The toxicity of the QDs in THP-1 leukemic cells was also studied. Results showed that the 8ZnO/2Ag ratio was the most effective since it had high antibacterial capacity against Mtb both in vivo and in vitro but without affecting the cellular viability of THP-1 cells [ 81 ]. In 2016, R. Jalal et al used different techniques (fluorescence and scanning electron microscopy, flow cytometry and DNA extraction) to elucidate the mechanism of action of ZnO QDs administered alone and in combination with two antibiotics ciprofloxacin and ceftazidime.…”
Section: Zno Nanoplatforms For Bacterial Infectionmentioning
confidence: 99%
“…On the other hand, using just silver nanoparticles may be ineffective against some bacteria, because the antibacterial properties of silver nanoparticles are weak. Based on previous studies, synergistic effects of silver and zinc oxide nanoparticles (AgZnONPs) have been proven effective on various bacteria . Zinc oxides has been recognized as antibacterial material in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, studies have suggested the ability of Ag-ZnO NPs to inhibit the growth of the standard laboratory strain of M. tuberculosis H37Rv 32. However, there is no sufficient data regarding the antibacterial effects of Ag, ZnO, and Ag-ZnO NPs against the drug-resistant clinical strains of M. tuberculosis .…”
Section: Discussionmentioning
confidence: 99%